Slavoj Žižek - Myers, Tony, 1969- (London ; New York : Routledge, 2003)
"Slavoj Zizek is no ordinary philosopher. Approaching critical theory and psychoanalysis in a recklessly entertaining fashion, Zizek's critical eye alights upon a bewildering and exhilarating range of subjects, from the political apathy of contemporary life, to a joke about the man who thinks he's a chicken, from the ethicial heroism of Keanu Reeves in speed, to what toilet designs reveal about the national psyche. Tony Myers provides a clear and engaging guide to Zizek's key ideas, explaining the main influences on Zizek's thought, most crucially his engagement with Lacanian psychoanalysis, using examples drawn from popular culture and everyday life." "Slavoj Zizek is essential reading for anyone wanting to understand the thought of the critic whom Terry Eagleton has described as "the most formidably brilliant exponent of psychoanalysis, indeed of cultural theory in general, to have emerged in Europe for some decades.""--BOOK JACKET.
Why Zizek? -- When Zizek shudders (we don't have to): popular culture and philosophy? -- Is this not the way to read Zizek? -- Subject of a biography: biography of a subject -- This book -- -- Key ideas -- Who are Zizek's influences and how do they affect his work? -- Zizek's influences: philosophy, politics and psychoanalysis -- Hegel -- Marx -- Lacan -- The imaginary -- The symbolic -- The real -- The philosopher of the real -- -- What is a subject and why is it so important? -- The cogito -- The cogito and the post-structuralists -- Madness: the vanising mediator between nature and culture -- The birth of God: reading the cogito via Schelling -- From subject to subjectivization -- -- What is so terrible about postmodernity? -- The postmodern risk society -- The disintegration of the big other -- The postmodern superego: enjoy! -- Keeping it real: the return of the other -- The act -- -- How can we distinguish reality from ideology? -- False consciousness and cynicism -- Belief machines -- The three modes of ideology -- The spectre that haunts reality -- What is the relationship between men and women? -- The formulae of sexuation -- 'Woman does not exist' -- 'Women is a symptom of man' -- 'There is no sexual relationship' -- -- Why is racism always a fantasy? -- 'Che vuoi?': 'what do you want from me?' -- Looking through the fantasy window -- The ethnic fantasy -- The ethics of fantasy -- -- After Zizek -- The curse of Jacques: limitations on the influence of Zizek -- Leftism -- Universal criticism -- The retroactive Zizek
Includes bibliographical references (p. [127]-138) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Žižek, Slavoj; Zizek, Slavoj; Žižek, Slavoj; Electronic books